MODIFIKASI MESIN AUTOLATHE PADA PLC LG MASTER K200S DI PT FSCM MANUFACTURING INDONESIA - Lin Prasetyani; Nicodemus Okky (Politeknik Manufaktur Astra, 2013)
At PT FSCM Manufacturing Indonesia autolathe machine is a machine used for the production of joint pin. Joint pin is used as a component manufacturer that serves as a connecting link drive chain connector. The production capacity of the engine joint pin autolathe less of the total production in the PT FSCM Manufacturing Indonesia every month. This problem may be overcome by reducing process steps autolathe engine and reduce the time required for a single pin joint production cycle. Improvements made include the addition of reed switches, solenoid valve replacement, and modification of PLC program LG Master K200s. Autolathe engine capacity that previously could produce 11.970pcs/hari be 21,280 pcs / day.